Integrasi Nilai Pancasila dalam Literasi Keuangan Digital: Tinjauan Pendidikan Kewarganegaraan Modern - Ahmad Muhamad Mustain Nasoha; Ratna Ayu Fitriana; Bintang Mufidia Rizqi; Rifania Halimatussakdiah (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study explores how Pancasila values can be integrated into digital financial literacy through the lens of modern civic education. It is grounded in the urgency to cultivate national values that shape individuals who are both digitally skilled and socially responsible. In an era of globalization and rapid technological change, managing digital finance requires more than technical ability—it demands moral integrity and ethical awareness. The study aims to discover effective strategies for embedding Pancasila principles into digital financial literacy to strengthen citizens’ awareness and competence in navigating digital challenges. Using a qualitative method with content analysis of educational policies and literature, the research seeks to develop a learning model that harmonizes Pancasila and digital finance education in schools and society. The findings indicate that integrating Pancasila values enhances ethical, inclusive, and independent dimensions in digital financial literacy, contributing to sustainable civic character formation. These values encourage critical thinking, empathy, and social responsibility in financial technology use. In conclusion, combining civic education with Pancasila-based digital financial literacy is essential for fostering a financially literate generation rooted in ethics, integrity, and concern for collective welfare in the digital era.